1990
DOI: 10.1017/s0033291700017207
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and medical consultation in primary care settings

Abstract: SynopsisThis paper examines the effect of psychiatric morbidity, as measured by the GHQ-60, on the probability of being in contact with a primary care physician, and the socio-demographic factors which influenced this effect. We found that the presence of psychiatric morbidity emerged as a major determinant of primary care utilization in both sexes, and about one-sixth of consultations in men and one-fifth of consultations in women could be attributed to it. Logistic modelling was used to investigate the joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
4

Year Published

1992
1992
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 24 publications
4
19
0
4
Order By: Relevance
“…Thus, patients presenting to emergency departments for their first attack, though not severe, may lead physicians to the recognition of panic. The association of other panic severity measures with being told is consistent with previous work that reported that recognition is associated with levels of distress [Vazquez-Barquero et al, 1990], symptom severity [Roy-Byrne et al, 2000], and anxiety. However, unlike previous studies, recognition was not associated with demographic variables [Dammen et al, 1999] or severity of medical illness [Roy-Byrne et al, 2000].…”
Section: Discussionsupporting
confidence: 88%
“…Thus, patients presenting to emergency departments for their first attack, though not severe, may lead physicians to the recognition of panic. The association of other panic severity measures with being told is consistent with previous work that reported that recognition is associated with levels of distress [Vazquez-Barquero et al, 1990], symptom severity [Roy-Byrne et al, 2000], and anxiety. However, unlike previous studies, recognition was not associated with demographic variables [Dammen et al, 1999] or severity of medical illness [Roy-Byrne et al, 2000].…”
Section: Discussionsupporting
confidence: 88%
“…They are clinically heterogeneous exhibiting higher rates of non disease-specific physical and chronic illness [7,[11][12][13]. Higher rates of FA are found in association with mental illness [11,[14][15][16][17][18][19], the likelihood of FA increasing with anxiety disorder by a factor of 1.14 in a multi-adjusted model [19]. FAs also have higher rates of depressive symptoms [15,16,20,21], as well as somatoform symptoms or disorders [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Such comparisons include irritable and in flammatory bowel disease [27], fibromyalgia and rheumatoid arthritis [19], or dyspepsia and peptic ulcer [38], Other populations in volve not diseases but symptoms, such as chronic pain [39] or tinnitus [40], Another source of variance has been the timeline of research. Some studies focus on the early stages of health-seeking behavior in primarycare medical settings [41][42][43], while others deal with the later stages of chronic disease. One study compared response to an acute with response to a chronic condition, in this case wrist fracture with stroke [44], An inter esting methodologic innovation has been at tention to a critical juncture in the natural his tory of a disorder in order to observe the 'at risk' role [45], for example following detec tion of a lump in the breast or recurrence of myocardial infarction [46], One important emphasis has been the widespread use of experimental designs to study cognitive factors in response to the threat of illness.…”
Section: Methodsmentioning
confidence: 99%